Treatment under general anesthesia after dental trauma in a patient with autism spectrum disorder: a case report - Mariamelya CAMPOS; Saulo Vinicius da ROSA; Marina Luísa Garbarino NOGUEIRA; Margareth Eliana Dias CONSULIN; Luiz Gabriel SIGNORELLI; Tatiane MAREGA; Alcides Ricardo GONÇALVES (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT The objective of this study was to present a clinical case of a pediatric patient with ASD who had experienced dental trauma and underwent dental treatment in a hospital environment under general anesthesia. A 10-year-old male patient who was Brazilian and had leukoderma was diagnosed with ASD at three years of age, he experienced trauma to the upper teeth, with avulsion of tooth 12 and extrusive displacement of tooth 11, after being run over by a car in February 2017. He was immediately taken to the emergency room, where he was seen by a dentist and he was immediately transferred to Hospital. In the out-patient clinic of this hospital, with the aid of protective stabilization and infiltrative anesthesia, tooth 12 was reimplanted 40 minutes after trauma and restrained with composite resin. He continued treatment in another city and Endodontic and paraendodontic treatment of teeth 11 and 12 was performed under general anesthesia. Follow-ups with the patient are continuing, with the last control periapical radiograph taken in January 2020. In this case, the proposed dental treatment was successful and did not lead to any complications.